Abandono familiar y su incidencia en la conducta de un adolescente de 14 años de edad del cantón Babahoyo - Rebolledo Litardo, Erika Graciela (2021)
Talking about abandonment encompasses a complex dimension about the needs and rights that deserve to be covered in an individual to be able to consider a “personal wellbeing” since the family environment plays a very important role in the sociocultural development even more in children and adolescents, since in this context they obtain their information, that is, they acquire their habits, principles, customs. Therefore, your emotions, thoughts and behavior will depend on that, resources that need to be positive to face the adversities of life after experiencing abandonment. However, other factors must be considered, such as: lack of responsibility, illness, migration by parents and divorces. When speaking of abandonment, it should be considered that it is a form of violence against human rights.